Comparative Study of the Optical and Heat Generation Properties of IR820 and Indocyanine Green - Alicia Fernandez-Fernandez; Romila Manchanda; Tingjun Lei; Denny A. Carvajal; Yuan Tang; Syed Zahid Raza Kazmi; Anthony J. McGoron (Molecular Imaging)
Near-infrared (NIR) fluorophores are the focus of extensive research for combined molecular imaging and hyperthermia. In this study, we showed that the cyanine dye IR820 has optical and thermal generation properties similar to those of indocyanine green (ICG) but with improved in vitro and in vivo stability. The fluorescent emission of IR820 has a lower quantum yield than ICG but less dependence of the emission peak location on concentration. IR820 demonstrated degradation half-times approximately double those of ICG under all temperature and light conditions in aqueous solution. In hyperthermia applications, IR820 generated lower peak temperatures than ICG (4–9%) after 3-minute laser exposure. However, there was no significant difference in hyperthermia cytotoxicity, with both dyes causing significant cell growth inhibition at concentrations ≥ 5 μM. Fluorescent images of cells with 10 μM IR820 were similar to ICG images. In rats, IR820 resulted in a significantly more intense fluorescence signal and significantly higher organ dye content than for ICG 24 hours after intravenous dye administration ( p < .05). Our study shows that IR820 is a feasible agent in experimental models of imaging and hyperthermia and could be an alternative to ICG when greater stability, longer image collection times, or more predictable peak locations are desirable.